Calibrating Your Intuition : Capital Allocation for Market and Credit Risk - Kupiec, Paul (IMF Working Papers; Working Paper ;, 2002)
Value-at-Risk (VaR) models often are used to estimate the equity investment that is required to limit the default rate on funding debt. Typical VaR "buffer stock" capital calculations produce biased estimates. To ensure accuracy, VaR must be modified by: (1) measuring loss relative to initial market value; and (2) augmenting VaR to account for the interest income required by investors. While this issue has been identified in the market risk setting, it has yet to be recognized in the credit risk literature. Credit VaR techniques, as typically described, are not an appropriate basis for setting equity capital allocations.